2007
DOI: 10.1111/j.1547-5069.2007.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence, Spirituality, Stress and Quality of Life in Chronic Illness

Abstract: Psychosocial factors are important in patients' cognitive interpretations of illness. SOC and spirituality may buffer stress in the context of chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 15 publications
6
94
0
6
Order By: Relevance
“…Higher SOC indicates an ability to cope with adversities such as war (Braun-Lewensohn & Sagy, 2014). Kimhi,Dror & Sterne 39 Results have indicated that higher SOC has been associated positively with protective factors (Ebert, Tucker, & Roth, 2002), and negatively with risk factors (Delgado, 2007), as well as laboratory induced stress (Kimhi, 2015). We assumed that SOC would positively predict resilience among both Jews and Israeli Arabs.…”
Section: Psychological Resiliencementioning
confidence: 99%
“…Higher SOC indicates an ability to cope with adversities such as war (Braun-Lewensohn & Sagy, 2014). Kimhi,Dror & Sterne 39 Results have indicated that higher SOC has been associated positively with protective factors (Ebert, Tucker, & Roth, 2002), and negatively with risk factors (Delgado, 2007), as well as laboratory induced stress (Kimhi, 2015). We assumed that SOC would positively predict resilience among both Jews and Israeli Arabs.…”
Section: Psychological Resiliencementioning
confidence: 99%
“…There is a body of literature highlighting the association of various coping strategies with adjustment, and acceptance of one's condition is an important basis for adapting to and coping with the condition (see, for example Felton and Revenson, 1984;Kendal and Buys, 1998;Delgado, 2007;Livneh and Antonak, 2007;among others). For participants in this study, the knowledge that generations of people, including their own ancestors, have faced similar disease in old age and that the rituals of their culture have proven valuable as a means for coping is a source of comfort and also a pattern for behavior in the context of serious illness.…”
Section: Cultural Understanding and Adjustment To Cvd Among Elderly Gmentioning
confidence: 99%
“…In relation to elderly individuals, coping in the context of 'successful aging' has often been linked to the avoidance of disease and disability (Rowe and Kahn, 1987), although cognitive factors and a high level of social engagement are often included (Young, Frick and Phelan, 2009). A strong sense of coherence and personal spirituality have, for older populations, been associated with better coping and enhanced quality of life in chronic illness (Delgado, 2007).…”
Section: Adjustment To Life With Illnessmentioning
confidence: 99%
“…과 스트레스에 영성이 완충작용을 하며 (Delgado, 2007), 환자 PTSD (Bormann, Thorp, Wetherell, & Golshan, 2008) 에게 영성 중심의 집단중재로 스트레스 감소에 효과가 있음 (Malinski, 2002). …”
Section: 스트레스와의 연관성에 대해서는 환자의 삶의 질 Copdunclassified